Filsafat dan Teknologi: Menelusuri Dampak Digitalisasi pada Pemikiran Filosofis - Afrida Naily A'la; Ninda Nurul Fadhilah; Esty Cahyaningsih; Rahmawati (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to explore the relationship between philosophy and technology in the context of the increasingly deep digitalization of modern society. With the advancement of information and communication technology, philosophical thought has undergone a significant transformation, both in the way we understand basic concepts such as existence, knowledge, and ethics, and in philosophical practice itself. This study analyzes the impact of digitalization on critical thinking methods and philosophical reflection, and how digital platforms facilitate dialogue and collaboration between thinkers from various backgrounds. In addition, this study also examines the challenges faced by philosophy in dealing with new issues that arise due to technological developments, such as privacy, digital identity, and artificial intelligence. With an interdisciplinary approach, this study is expected to provide new insights into the role of philosophy in understanding and directing the impact of technology in everyday life.